COSMETIC OUTCOME OF AUTOGENOUS DERMIS FAT GRAFT AS AN ORBITAL IMPLANT AFTER ENUCLEATION - Kamil, Zeeshan; Qurban, Qirat (Journal of Ayub Medical College Abbottabad, 2022)
The surgical method of removing the complete intact globe while leaving the extraocular muscles and orbital fat behind is called as enucleation. The intention behind this study is to share the experience of autogenous dermis fat graft as an orbital implant following enucleation and its cosmetic outcome. It was a prospective study conducted at the Orbit and Oculoplastic department of LRBT Tertiary Teaching Eye hospital from July 2018 to June 2019. Eighty-five patients were recruited for this study belonging to either gender with ages ranging from 20 to 50 years. None of the recruited patients had undergone prior enucleation or evisceration. All the patients were informed and counseled about the surgical modus operandi and the expected outcomes and verbal consent was taken from each patient along with approval from the hospital's ethical review committee before proceeding with the surgery. Every participant underwent primary enucleation followed by autogenous dermis fat graft orbital implant and followed up for duration of up to 3 months after the surgical procedure. Results: At ninety days after the procedure, 78.2% of patients had a very good cosmetic result. Conclusion: The placement of autogenous dermis fat graft as an orbital implant following primary enucleation has a good accomplishment rate with excellent cosmetic outcome.